A Cloning Issue of Sacrifice Animals (Qurban) in Biology Teachers' Argumentation in Islamic Organization-Based Senior High Schools - Afridha Laily Alindra; Ari Widodo; Taufik Rahman; Riandi Riandi (LPPM UIN K.H. Abdurrahman Wahid Pekalongan, 2022)
One of the exciting topics in the socio-scientific issue is cloning. This issue is seen as a debatable issue in religion and science. In the practice of science learning in class, Biology teachers are required to be able to present this topic proportionally. This research aims to study how the arguments of Biology teachers in Islamic organization-based senior high schools in Indonesia face the cloning issue of sacrificed animals. This research was conducted in three Islamic organization-based senior high schools. This research uses the qualitative method by observation process on the learning of cloning topic in the class, questionnaire, and an in-depth interview with Biology teachers of XII grade from the three different schools in Banten Province, Indonesia. Results of the research show that related to the cloning issue of sacrifice (Qurban) animals is not only related to the religious aspect; there is the existence of specific argumentation patterns in the mind of the teachers. The designs are presented in the frameworks of economic (Organization A), social humanity (Organization B), and knowledge (Organization C). These three frameworks of organization give the primary colors for each teacher's argumentation. Thus, further studies must explore the effects of Islamic organizations on the arguments and the practice of cloning topic teaching at Islamic organization-based senior high schools.